2008
DOI: 10.1074/jbc.m802904200
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 Mediates the Interaction between STIM1 and hTRPC1 and Regulates the Mode of Activation of hTRPC1-forming Ca2+ Channels

Abstract: Orai1 and hTRPC1 have been presented as essential components of store-operated channels mediating highly Ca(2+) selective I(CRAC) and relatively Ca(2+) selective I(SOC), respectively. STIM1 has been proposed to communicate the Ca(2+) content of the intracellular Ca(2+) stores to the plasma membrane store-operated Ca(2+) channels. Here we present evidence for the dynamic interaction between endogenously expressed Orai1 and both STIM1 and hTRPC1 regulated by depletion of the intracellular Ca(2+) stores, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 50 publications
(58 reference statements)
4
107
0
Order By: Relevance
“…Orai1 was also shown to be associated with the complex formed by STIM1 and TRPC. Hence, the idea emerged that the function of TRPC channels might well depend on their association or not with the STIM/Orai molecules [30][31][32][33][34][35]. Our experimental evidence suggested that TRPC3 function independently from STIM/Orai and that its activity is not linked to the Ca 2+ content of the store.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Orai1 was also shown to be associated with the complex formed by STIM1 and TRPC. Hence, the idea emerged that the function of TRPC channels might well depend on their association or not with the STIM/Orai molecules [30][31][32][33][34][35]. Our experimental evidence suggested that TRPC3 function independently from STIM/Orai and that its activity is not linked to the Ca 2+ content of the store.…”
Section: Discussionmentioning
confidence: 79%
“…Antisense From siRNA STIM1 GGCUCUGGAUACAGUGCUCtt GAGCACUGUAUCCAGAGCCtt Ambion Orai1 CGUGCACAAUCUCAACUCGtt CGAGUUGAGAUUGUGCACGtt Ambion TRPC1 CGGACUUCUAAAUAUGCUAtt UAGCAUAUUUAGAAGUCCGAAtt Oiagen TRPC3 GCAGCAGCUCUUGACGAUCUGGUAU AUACCAGAUCGUCAAGAGCUGCUGC Invitrogen TRPC4 UGUCUAUGUUGGAGAUGCUCUAUUA UAAUAGAGCAUCUCCAACAUAGACA Invitrogen TRPC5 CCCAAGUCAUUUCUAUACCUUGGUA UACCAAGGUAUAGAAAUGACUUGGG Invitrogen TRPC6 CCCAAGGAAUAUUUGUUUGAGUUGU ACAACUCAAACAAAUAUUCCUUGGG Invitrogen PKC CCAGAUUUGUGGCUUAUAAtt UUAUAAGCCACAAAUCUGGtt Qiagen PKC␦ GCCGGGACACUAUAUUCCAtt UGGAAUAUAGUGUCCCGGCUtt Ambion PCR primers STIM1 TGACAGGGACTGTGCTGAAG AAGAGAGGAGGCCCAAAGAG Invitrogen Orai1 GCTCATGATCAGCACCTGCAC GGGACTCCTTGACCGAGTTG Invitrogen TRPC1 GAGGTGATGGCGCTGAAGG GCACGCCAGCAAGAAAAGC Invitrogen TRPC3 CTGGCTCTGCTTGTGTTCAATG AGTCAGTAACTGTGATATTGGATATTG Invitrogen TRPC4 TCAGCACATCGACAGGTCAGAC CCACGGTAATATCATCCACTCGAC Invitrogen TRPC5 CTCTGATTGCGGAAGCCTCT GCAACGAACTTAAAATGTTGGATATTG Invitrogen TRPC6 AAGTATAAGGAGCTCAGAAATTTCCAT TCTGATATTGTCTTGGAGGATTATTGA Invitrogen GusB CCACCAGGGACCATCCAAT AGTCAAAATATGTGTTCTGGACAAAGTAA Invitrogen TBP GCCCGAAACGCCGAATATA CGTGGCTCTCTTATCCTCATGA Invitrogen GAPDH GCACAAGAGGAAGAGAGAGACC AGGGGAGATTCAGTGTGGTG Invitrogen EE-EF1 AGCAAAAATGACCCACCAATG GGCCTGGATGGTTCAGGATA Invitrogen reported that Orai1 and TRPC proteins form complexes together with STIM1 that participate to Ca 2+ entry [30][31][32][33][34][35].…”
Section: Sensementioning
confidence: 99%
“…Several studies show that association between TRPC1 and STIM1 increases following store depletion (6,16,19,20), although a recent study was unable to demonstrate this (21). While the ezrin/radixin/moesin (ERM) domain of STIM1 appears to bind to TRPC1, the C-terminal 684 KK 685 residues are involved in gating the channel via electrostatic interaction with TRPC1( 639 DD 640 ) (8,13).…”
mentioning
confidence: 99%
“…The nature of the plasma membrane Ca 2ϩ permeable channels involved both in ROCE and SOCE are still under investigation but most studies have presented Orai1 as a putative SOC channel (9 -14) and transient receptor potential (TRP) proteins as candidates to mediate both SOCE and ROCE (15-20). These channels have been shown to take part in signaling complexes, including the protein STIM1, which might be essential for the activation mode of the channel (19,(21)(22)(23).…”
mentioning
confidence: 99%
“…The nature of the plasma membrane Ca 2ϩ permeable channels involved both in ROCE and SOCE are still under investigation but most studies have presented Orai1 as a putative SOC channel (9 -14) and transient receptor potential (TRP) proteins as candidates to mediate both SOCE and ROCE (15-20). These channels have been shown to take part in signaling complexes, including the protein STIM1, which might be essential for the activation mode of the channel (19,(21)(22)(23).In addition, a functional interaction between IP 3 Rs and human TRP channels has been demonstrated by different approaches in several cell types, including human platelets endogenously expressing TRPC1 and IP 3 Rs (24, 25), human embryonic kidney (HEK)-293 cells stably expressing hTRP3 (26) or TRPC1-6 proteins (27), and HEK293T transiently expressing different TRP proteins (28). IP 3 Rs have also been shown to be required for activation of TRPC1 in vascular smooth muscle cells (29) and for the IP 3 -dependent miniature Ca 2ϩ channels (I min ), a Ca 2ϩ -selective channel activated by store depletion, in excised membrane patches from A431 human carcinoma cells (30).…”
mentioning
confidence: 99%